Effect of solid and liquid media inoculations of spawn on yield and quality parameters of oyster mushrooms (Pleurotus ostreatus) grown on different substrate in Guyana - Sharisa Slowe; Diana Seecharran; Ansari, Abdullah Adil; Sirpaul Jaikishun; Kumar Latchman (Mushroom Research, 2024)
Oyster mushrooms (Pleurotus ostreatus) convert lignocellulosic materials present in agricultural waste into high quality protein rich food. This study investigated the yield performance of P. ostreatus on different substrate such as wheat straw, paddy straw, and sugarcane bagasse. A total of three trials were conducted with solid and liquid media inoculum: trials 1 and 2 were inoculated with liquid oyster mushroom culture, while trial 3 was inoculated with oysters’ mycelium grown on a petri dish.  In trial 1, wheat straw substrate produced the most fruiting bodies with the highest average pin yield, but sugarcane bagasse produced mushrooms with the excellent fruit body quality. Paddy straw had the greatest pin yield in trial 2, but sugarcane bagasse produced the most fruiting bodies, and wheat straw substrate produced mushrooms with the best fruit body quality. However, in trial 1 and 2, results were at par statistically. In trial 3, Only paddy straw substrate produced fruiting bodies. Elemental analysis of the mushrooms harvested produced variable results. For trial 1, sugarcane bagasse produced mushrooms with the highest calcium content, whereas mushrooms grown in wheat straw substrate had the highest iron and copper content. The opposite results are seen in trial 2 where mushrooms cultivated in sugarcane bagasse had the highest iron and copper content, and wheat straw substrate produced mushrooms with very high calcium content. Elemental analysis of the substrates before cultivation showed that wheat straw had the highest average calcium concentration, whereas sugarcane bagasse initially had the highest iron content and copper content. After harvesting, sugarcane bagasse substrate had the highest average calcium content, while paddy straw substrate had the highest average iron and copper content. Our data suggest that growth parameters are affected by the type of substrate. We suggest exploring the substrate combinations for mushroom cultivation to increase the yield of mushroom fruiting bodies and their growth parameters.